ALEMTUZUMAB: LONG TERM FOLLOW-UP IN A SINGLE CENTRE COHORT. Issue 10 (9th September 2014) - Willis, Mark; Harding, Katharine; Wardle, Mark; Pickersgill, Trevor; Tomassini, Valentina; Robertson, Neil
Abstract : Introduction: Alemtuzumab is an anti-CD52 monoclonal antibody, approved for the treatment of relapsing multiple sclerosis (RMS). However, it has significant side effects and long-term follow-up is required to provide accurate information for patient management and counselling. Methods: Patients were followed prospectively within an active surveillance program and standardised data collected on a regional database. Data on patient demographics, adverse events, disability trajectories (EDSS), relapses and retreatment intervals were analysed. Results: 96 patients with highly active RMS were identified (69F:27M). Mean follow-up post treatment was 5.1 years. Most patients received 2 annual cycles but 27 (28.1%) received 3, 7(7.3%) received 4 and 2 (2.1%) received 5. Pre- and post-treatment annualised relapse rates were 2.1 and 0.4 respectively. Mean change in EDSS from baseline was 0.44. 8 patients developed secondary progression a mean of 2.8 years post treatment. A range of autoimmune disorders (AID), notably thyroid disease was identified in 45 (47%). Discussion: Our data supports the effectiveness of alemtuzumab in patients with RMS in reducing relapse rates. However, despite a paucity of inflammatory disease activity, disability accumulation continued in some patients. Overall retreatment rate was 37.5% and AID, whilst common, could be effectively identified through routine surveillance processes and managed without serious consequence.